Beyond COVID-19: A Feminist Plan for Sustainability and Social Justice - United Nations Women (United Nations, 2021)
As the world learns to live with COVID-19, to emerge from the current crisis, and to “build back better”, UN Women’s new Feminist Plan for Sustainability and Social Justice is a visionary but practical roadmap for putting gender equality, social justice, and sustainability at the centre of the recovery. The Feminist Plan maps the ambitious and transformative policies – on livelihoods, care, and the environment – that are needed to build a more equal and sustainable future. To get there, calls for context-specific policy pathways, tailored political strategies, and financing. The plan identifies key levers that can create change and the actors at global, national, local levels that need to take action to move towards this vision.